Cohen : conteur oriental ? - Stachová, Klára (Verbum – Analecta Neolatina, 2006)
The present paper deals with the work of Albert Cohen and how it is influenced by orality. Albert Cohen was inspired by the style of the stories in the The Book of Thousand Nights and One Night in a way that we can call his technique "orientalizing". After a methodological introduction concerning the conception of orality, we discuss the indications of orality at the various structure levels of Cohen’s text: the extradiegetic narrator (Cohen dictated his texts to "the women of his life" and used the method of improvisation), the elocutio (characters are differentiated on the basis of their utterances; the style demonstrates clichés and idiomatic expressions), the construction of the plot (the hero follows the traditional journey), and the alternation of the narrative levels (extradiegetic and diegetic). Finally, we determine the functions of orality in Cohen’s work and the author’s intention.